Max Weber and Institutional Theory - Lepsius, M. Rainer (Springer International Publishing : Imprint: Springer, 2017)
This book presents a collection of essays on institutional theory written by the German sociologist and Weber-expert M. Rainer Lepsius. Based on Weber's work, the author develops concepts of institutional theory, which he subsequently applies to topics such as National Socialism, democratization processes, German unification, and the institutionalization of the European Union. By showing how charismatic leadership can under certain circumstances threaten democratic structures and curtail individual freedoms, and by analyzing the structural and cultural conditions under which people develop trust in political and social structures and ultimately come to support and comply with them, the author provides a sound analytical understanding of the development of democratic institutions and a democratic political culture. This collection of essays was edited, translated and commented on by Claus Wendt.
Keywords: Social sciences.; Political science.; Religion and culture.; Social sciences -- Philosophy.; Political sociology.; elektronické knihy; electronic books